DESKRIPSI PERSEPSI DAN EFEKTIVITAS DISKUSI KELOMPOK TERFOKUS DALAM MENGUBAH PERSEPSI REMAJA TERHADAP PENGGUNAAN VAPE - hardiyanto, hardiyanto (Jurnal Keperawatan Malang, 2024)
Background. The popularity of e-cigarettes is skyrocketing, supported by the availability of various device technologies. Many people are interested in e-cigarettes because they are considered a tool to help those who are addicted to smoking. However, information about nicotine levels and other information is often inaccurate and far from the actual situation. Objectives. This study aim is to look the description of adolescents' perceptions of e-cigarettes and to determine the effectiveness of Focused Group Discussion in changing adolescents' perceptions. Methods. This study is a quantitative study with 117 respondents and a pre-post intervention questionnaire was conducted using 20 respondents who were e-cigarette/vape users. Respondents were given a questionnaire before the intervention in the form of health education using data from journals. Results. Before the intervention, adolescents in the study had a Fair perception of e-cigarettes/vaping (100%), while after the intervention all respondents were in a Good Perception (100%). Implication. There are many adolescents that do not have the correct perception of the dangers of e-cigarettes/vape. There needs to be creative health education that can reach adolescents widely to reduce the impact of the development of e-cigarette/vape use. Keywords: Electronic Cigarettes; Focus Group Discussion; Perception,